Prevention of venous thromboembolism in obesity. (December 2010) - Freeman, Andrew L; Pendleton, Robert C; Rondina, Matthew T
Venous thromboembolism (VTE) is a significant cause of morbidity and mortality in hospitalized patients. Where appropriate, evidence-based methods of prophylaxis are implemented and the burden of VTE can be reduced substantially. Obesity, including morbid obesity, is associated with a high risk of VTE and, unfortunately, fixed doses of US FDA-approved anticoagulant regimens, including unfractionated heparins, low-molecular-weight heparins and factor Xa inhibitors, may not provide optimal VTE prophylaxis in these patients. Although the data are still limited, a rapidly growing body of literature and cumulative evidence suggests that anticoagulant dose adjustments in morbidly obese patients may optimize pharmacodynamic activity and reduce VTE risk. With the prevalence of morbid obesity continuing to rise, more high-quality clinical data are needed to better understand the pathobiology of VTE in obesity and provide effective, yet safe, prevention strategies.